Peran Organisasi Internasional di Dalam Suatu Negara - Adelia Z, Carissa; Salsabila A, Auroria; Sari, Putri Tiara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
An international organization is an association formed and supported by several countries with the aim of maintaining world peace in terms of international relations. Since World War I, precisely at the beginning of the 19th century, two international organizations emerged under the auspices of the UN, namely the Telegraphic Union (1985) and the Universal Postal Union (1874). Each country certainly has different goals and aspirations in developing its country. One of them is becoming part of an international organization. The role of a country's international organization is to establish positive cooperation to develop the country. Apart from that, there are types of organizations and characteristics and benefits of countries joining international organizations.